EXPERENTIAL MARKETING AND SERVICE QUALITY ON WOM RECCOMENDATION THROUGH SATISFACTION AS MEDIATION VARIABLE OF RUDANA MUSEUM,BALI - Erny Hutabarat; Eriq Suweta (President University, 2021)
The purpose of this study was to determine the influence of experiential marketing and service quality towards the WOM recommendation with satisfaction as variables of mediation at the Sangiran Museum Sragen visitors. The population in this study is the visitor Rudana museum. Sampling technique using purposive sampling and obtained a sample of 200 respondents who had visited for the second times or more. This research variable uses three variables of dependent variable, independent variable, and mediation variable. For the dependent variable(Y) of this study is the wom recommendation. For independent variables include: experiential marketing (X1) and service quality (X2) and mediation variables are satisfaction (Z). The method is used quantitative research method with 200 respondents; data were collected and analyzed using SPSS and SmartPLS 3.2.8. The results indicated that (1) experiential marketing has an effect on satisfaction; (2) the service quality has an effect on the satisfaction; (3) satisfaction effect on recommendation; (4) experiential marketing has an effect on the recommendation; (5) service quality service has no direct effect on the wom recommendation;(6) experiential marketing and service quality has an effect on recommendations with satisfaction as mediation variables.Keywords: Experiential Marketing, Service Quality, Satisfaction, WOM Recommendation